Bazyli Wielki jako spadkobierca i kontynuator greckiej tradycji filozoficznej w homili "O zawiści" - Sowa, Joanna (Vox Patrum, 2022)
The aim of this article is to present the role played by the Greek moral philosophy in Basil of Cesarea’s homily On envy. The homily, which has been classified as one of the moral treatises, deals with the problem of the nature and the cure of envy, recognized by Greco-Roman and early Christian thinkers alike as a particularly dangerous and destructive emotion both for the soul of the individual human being and the society as a whole. Episcopal writers appropriated much of the traditional language and conceptualization of invidious emotions but also adjusted them to their own purposes and added their own insights to longstanding interpretive traditions. Although Basil himself never named in the homily other sources than the Bible, a careful analysis of the text shows the strong influence of the Greek philosophical writers of the past, especially Plato, Aristotle, Stoics, and Plutarch of Chaeronea.